BENEFITS OF DIGITAL BANKING - Abdurakhmonov Abdulaziz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
A digital bank is a bank or its subsidiary that provides remote banking services using innovative banking technologies. In this article, we will define the concept of "digital banking" using the example of the activities of ANOR BANK JSC and analyze the current state of digital banking services and the bank’s activities. Also, as a result of comparing the activities of traditional banks and digital banks operating in the country, conclusions were drawn about the development of banking services in the country.